Tomato and Melon Meloidogyne Resistant Rootstocks Improve Crop Yield but Melon Fruit Quality Is Influenced by the Cropping Season - Expósito, Alejandro; Pujolà, Montserrat; Achaerandio, Isabel; Giné, Ariadna; Escudero, Nuria; Fullana, Aïda Magdalena; Cunquero, Marina; Loza-Alvarez, Pablo; Sorribas, F. Javier (Frontiers in Plant Science, 2020)
Four rotation sequences consisting of ungrafted tomato cv. Durinta – melon cv. Paloma or tomato grafted onto the resistant rootstock ‘Aligator’– melon grafted onto the resistant Cucumis metuliferus accession BGV11135, and in reverse order, were conducted from 2015 to 2017 in a plastic greenhouse infested or not with Meloidogyne incognita to determine the plant tolerance (T), the minimum relative crop yield (m) and fruit quality. The relationship between M. incognita densities in soil at transplanting (Pi) of each crop and the crop yield was assessed and T and m were estimated by the Seinhorst’s damage model. In addition, the volume and the number of nuclei of single giant cells and the number of giant cells, its volume and the number of nuclei per feeding site in susceptible tomato and melon were compared to those in the resistant tomato and C. metuliferus 15 days after nematode inoculation in pot test. The relationship between the Pi and the relative crop yield fitted the Seinhorst’s damage model in both ungrafted and grafted tomato and melon, but not for all years and cropping seasons. The estimated T for ungrafted and grafted tomato did not differ but m was lower in the former (34%) than the latter (67%). Sodium concentration in fruits from ungrafted but not from grafted tomato increased with nematode densities in spring 2015 and 2016. The estimated ungrafted melon T did not differ from the grafted melon cultivated in spring, but it did when it was cultivated in summer. The relative crop yield of ungrafted melon was lower (2%) than the grafted cultivated in spring (62%) and summer (20%). Sodium concentration in melon fruits from ungrafted plants increased with nematode densities. No variations in fruit quality from grafted melon cultivated in spring were found, although less dry matter and soluble solid content at highest nematode densities were registered when it was cultivated in summer. Lower number of giant cells per feeding site was observed in both susceptible tomato germplasms compared to the resistant ones but they were more voluminous and held higher number of nuclei per giant cell and per feeding site.